16S ribosomal assay for early diagnosis of gonococcal meningitis with negative CSF culture: A case report. Issue 2 (February 2022) - Gao, Song; Xia, Lingyin; Huang, Meirong; Chen, Zehui; Chen, Anlin; Yang, Jianru; Min, Xun; Huang, Jian
Abstract: Gonococcal meningitis is an exceedingly rare infectious disease, and if not diagnosed and treated in time, it can be severe. We present a case of gonococcal meningitis occurring in a 31-year old healthy woman. She was admitted with fever and persistent headache without urogenital symptoms. Blood cultures were positive and identified as N.gonorrhoeae, but CSF and cervical secretions cultures were both negative. Further testing confirmed the presence of N.gonorrhoeae by 16S ribosomal gene amplification and sequencing in all samples. These results suggest that the case may be a disseminated infection caused by untreated gonorrhea. Our case also shows that nucleic acid detection plays an important role in the rapid and precise diagnosis of gonococcal meningitis and in finding the origin of the pathogen.